2020
DOI: 10.3390/nu12030614
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with a Mango Leaf Extract (Zynamite®) in Combination with Quercetin Attenuates Muscle Damage and Pain and Accelerates Recovery after Strenuous Damaging Exercise

Abstract: Prolonged or unusual exercise may cause exercise-induced muscle damage (EIMD). To test whether Zynamite®, a mango leaf extract rich in the natural polyphenol mangiferin, administered in combination with quercetin facilitates recovery after EIMD, 24 women and 33 men were randomly assigned to two treatment groups matched by sex and 5 km running performance, and ran a 10 km race followed by 100 drop jumps to elicit EIMD. One hour before the competition, and every 8 h thereafter for 24 h, they ingested placebo (72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…A number of recent studies have assessed the potential efficacy of a mango leaf extract standardized to a minimum of 60% mangiferin (Zynamite ® ). In terms of physical performance, several of these studies have assessed the ergogenic effects in humans of both acute [33][34][35][36] and longer-term supplementation [34] with this mango leaf extract combined with the polyphenols luteolin or quercetin. This research has demonstrated an improved performance during high intensity exercise [33][34][35], increased brain oxygenation [33,34], maximal aerobic capacity [33], increased muscle oxygen extraction [34,35] and the attenuation of muscle damage and improvements in the time course of decreased muscle performance [37].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have assessed the potential efficacy of a mango leaf extract standardized to a minimum of 60% mangiferin (Zynamite ® ). In terms of physical performance, several of these studies have assessed the ergogenic effects in humans of both acute [33][34][35][36] and longer-term supplementation [34] with this mango leaf extract combined with the polyphenols luteolin or quercetin. This research has demonstrated an improved performance during high intensity exercise [33][34][35], increased brain oxygenation [33,34], maximal aerobic capacity [33], increased muscle oxygen extraction [34,35] and the attenuation of muscle damage and improvements in the time course of decreased muscle performance [37].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional supplements were studied in four studies (33.2%) in this Special Issue [1,2,4,12]. Bazzucchi et al [1] and Martin-Rincon et al [4] have studied the effect of polyphenols on muscle recovery, EIMD, and muscle pain, with quercetin (Q) in monotherapy and quercetin plus Zynamite ® (mango leaf extract), respectively. Q is a flavonoltype polyphenol and Zynamite ® is a natural polyphenol; both have antioxidant and anti-inflammatory attributes that may stop EIMD and promote muscle recovery [1,4].…”
mentioning
confidence: 99%
“…Bazzucchi et al [1] and Martin-Rincon et al [4] have studied the effect of polyphenols on muscle recovery, EIMD, and muscle pain, with quercetin (Q) in monotherapy and quercetin plus Zynamite ® (mango leaf extract), respectively. Q is a flavonoltype polyphenol and Zynamite ® is a natural polyphenol; both have antioxidant and anti-inflammatory attributes that may stop EIMD and promote muscle recovery [1,4]. The supplementation with Q (1 gr/d) for 14 days following a double-blind crossover study design improve recovery from EIMD, the deterioration of neuromuscular function, and modulated the increase in muscular biomarkers such as creatine kinase (CK) and lactatedehydrogenase (LDH) [1] in healthy men.…”
mentioning
confidence: 99%
See 2 more Smart Citations